Extending the culture duration could not improve the culture positivity rate and clinical outcomes of periprosthetic joint infection - Wu, Baijian; Lin, Yuan; Su, Jinhui; Lin, Lan; Yu, Zhenggui; Zhang, Chaofan; Fang, Xinyu; Huang, Zida; Zhang, Wenming (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo explore the clinical value of extending the culture time for accurately diagnosing hip or knee PJI.MethodsThis retrospective study included 201 hip or knee PJI patients. All specimens were cultured using a standardized procedure. For all samples collected after January 2022, the extended culture period was 14 to 21 days. The detection accuracy and pathogen distribution of the standard culture duration (7 days) was compared with those extending.ResultsThe overall culture positivity rate was 89.05% (179/201). The most common pathogens were coagulase-negative staphylococci (CoNS, n=54) and methicillin-resistant Staphylococcus aureus (MRSA, n=26). Extending the culture duration did not significantly increase the culture positivity rate (89.05% vs. 89.06%, P=0.997), nor did it improve the infection control rate (89.05% vs. 85.94%, P=0.526). Further study revealed that extended results did not improve the diagnosis of PJI according to the Musculoskeletal Infection Society (MSIS) criteria in most patients with both positive standard and extended culture results (82.35%, 28/34). Four of the 5 patients with only positive extended culture results were diagnosed with PJI on the basis of a single positive culture result.ConclusionExtending the culture time didn’t significantly improve the clinical outcomes of PJI, rate of culture positivity or polymicrobial infection detection rate.